Review Paper on Data Mining and its Techniques and Mahatma Gandhi National Rural Employment Guarantee Act - Yadav, Kritika; Parmar, Mahesh (International Journal of Computer Sciences and Engineering, 2025)
Data Mining is a technique that attempts to find useful pattern from substantial volume of data. The paper reviews data mining and its techniques in e- governance. The paper also reviews the influence of the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) on the rural India. The objective of MGNREGA is to provide at least hundred days of job to the rural and tribal population, whose living entirely depends on daily wages. Moreover the paper gives the relative evaluation of numerous data mining methods and algorithms.